General characteristics of osteomyelitis in patients treated with dental implants - Falcon Guerrero, Britto (2021)
Osteomyelitis of the jaws is a relatively rare inflammatory process within the field of implantology and to characterize this pathology it is necessary to analyze not only the patient himself but also the clinical characteristics, pathological antecedents, etiology and treatment; with the intention of achieving an early diagnosis and thus avoiding the premature loss of dental implants. The objective of this review is to describe the general characteristics of osteomyelitis in patients treated with dental implants. Concluding that the general characteristics found can serve as support for an early diagnosis of osteomyelitis in relation to dental implants.